Benign ependymoma with extensive intracranial and spinal cerebrospinal fluid dissemination: case report and literature review. (4th May 2019) - Zhu, Fangmei; Ding, Jurong; Li, Yumei; Mao, Dewang; He, Xianglei; Chen, Wanyuan; Lou, Lin; Ding, Zhongxiang
Abstract: Myxopapillary ependymoma (MPE) is a rare variant of ependymoma that is most commonly located in the cauda equina and filum terminale. We present a case of 23-year-old man diagnosed with MPE in the fourth ventricle and sacral canal area with extensive disseminated lesions along the cerebrospinal ventricular system. Additionally, a molecular pathological diagnosis was performed. The patient underwent a craniotomy and a lumbar laminectomy. In the course of 18 months of follow-up, the patient have recovered very well.